(untitled) (ASEAN Engineering Journal, 2016)
Rapid urbanization in developing countries faces the challenge of increasing demand for urban water services. This challenge can be more significant particularly in urban coastal area under climate-related disaster, which is able to obviously influence the change of socioeconomic and environmental aspects. This study investigates the affected coastal community’s responses to water infrastructure under climate-related disaster in Tanjung Mas, located in the northern part of Semarang City, Central Java Province, Indonesia. Field observation, key informants interview, and structured household survey were conducted. The survey was conducted among 106 residents using random sampling method. The findings reveal that water infrastructure is mostly available in the study area and the residents typically rely on water source from the local water company by using water supply pipeline. However, the location in flood prone area has contributed enormously their vulnerability to water availability. The residents recognize the importance of water for their quality of life, and the impacts of urban development to reduce the availability of water resource, but they had not completely understood the relationship between climate change and water sector. They have perceived that climate change is not significant issue related to water resource, even though they live in prone area. The practice of their current measures is only able to cope with the impacts in the short term period, such as clearing drainage channels, adding sanitation infrastructure, and building simple embankment. Public awareness campaign and advocacy at the community level are necessary to reduce the low perception of potential risks posed by climate change and natural disasters related to water infrastructure. The specific government policy, program and practice oriented solutions on climate change and urban development issues need to be considered in order to increase resilience and sustainable urban development.